2011
DOI: 10.1016/j.rbmo.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

FSH modulatory effect on human granulosa cells: a gene–protein candidate for gonadotrophin surge-attenuating factor

Abstract: Previous evidence indicates a homology of gonadotrophin surge-attenuating factor (GnSAF) to the carboxyl terminal of human serum albumin (HSA) and the ability of human granulosa cells to produce mRNA transcripts corresponding to this fragment, but the underlying mechanism is still unknown. This study investigated the role of FSH in vitro in the expression of the carboxyl terminal of HSA by human luteinized granulosa cells. Cells were cultured on poly-l-lysine-coated microscope slides in the absence or presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The production of recombinant polypeptides corresponding to subdomain IIIB residues 490-585 of human serum albumin showed GnSAF bioactivity in vitro in a rat pituitary cellculture system (Tavoulari et al, 2004). Following this, the expression of human serum albumin mRNA was demonstrated in human luteinized granulosa cells (Karligiotou et al, 2006) and shown to increase under the influence of FSH (Karligiotou et al, 2011). Based on in-vitro experiments, GnSAF is not only different from inhibin, but also a unique substance that appears to have an important physiological role (Balen et al, 1995;Byrne et al, 1995;Pappa et al, 1999).…”
Section: Midcyclementioning
confidence: 96%
“…The production of recombinant polypeptides corresponding to subdomain IIIB residues 490-585 of human serum albumin showed GnSAF bioactivity in vitro in a rat pituitary cellculture system (Tavoulari et al, 2004). Following this, the expression of human serum albumin mRNA was demonstrated in human luteinized granulosa cells (Karligiotou et al, 2006) and shown to increase under the influence of FSH (Karligiotou et al, 2011). Based on in-vitro experiments, GnSAF is not only different from inhibin, but also a unique substance that appears to have an important physiological role (Balen et al, 1995;Byrne et al, 1995;Pappa et al, 1999).…”
Section: Midcyclementioning
confidence: 96%
“…The authors found that of the 13 exons known in the HSA gene (He and Carter, ), only exons 1–2 and 12–13 were expressed in granulosa cells. The same group later showed that FSH induces transcription of HSA exons 12–13 in granulosa cells isolated from follicular fluid, and Western blot analysis with polyclonal antiserum to the carboxyl‐terminus of HSA detected bands at 64 kDa as well as in the 12–14 kDa region (Karligiotou et al, ), which supports FSH as a modulator of GnSIF/AF, as first described by Koppenaal and coworkers (Koppenaal et al, ).…”
Section: Attempts To Identify Gsif/afmentioning
confidence: 65%
“…The Messinis group postulated that GnSIF/AF was an alternative form of HSA (Tavoulari et al, ; Karligiotou et al, ), and they performed Western blot assays and bioassays with polyclonal anti‐HSA antisera (purchased from Abcam, Cambridge, UK). A later study utilized a custom‐made rabbit antisera directed against the final 90 amino‐acid residues of HSA (Karligiotou et al, ). As above, the use of these polyclonal antisera was sufficient for Western blotting or blocking GnSIF/AF activity, but did not appear to be useful for immunopurification.…”
Section: Limitations To Identificationmentioning
confidence: 99%